EKSPERIMENTASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA KOMPUTER PADA MATERI POKOK PERSAMAAN GARIS LURUS DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS VIII SMP SURAKARTA - Hirtanto Hirtanto; Mardiyana Mardiyana; Imam Sujadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purposes of this research were to determine: 1) which students have better achievement in learning mathematics among Macromedia Flash and PowerPoint used as learning media 2) which students have better achievement in learning mathematics, ones with high, medium, or low learning motivation, 3) at each leaning by using media (Macromedia Flash and PowerPoint) which students have better achievement in learning mathematics, ones with high, medium, or low learning motivation, 4) at each of categories of learning motivation (high, medium, and low) which students have better achievement in learning mathematics, ones who are use Macromedia Flash or PowerPoint as learning media. The research was a quasi experimental. The population of this research was all students of grade VIII Junior High School of the Surakarta City, academic year 2011/2012. The samples in this research were 177 students taken by stratified cluster random sampling. Instruments used to collect data were mathematics achievement instrument test and questionnaires of student’s learning motivation instrument. Data analysis technique used hypothesis test with two-way analysis of variance with unbalanced cells resume test of multiple comparisons. From the results of the analysis, can be concluded that: 1) the learning achievement in mathematics of the students who were learning mathematics with macromedia flash were better than with powerpoint as learning media, 2) the learning achievement in mathematics of the students with the high learning motivation were better than the ones with the medium and low learning motivation, however the students with the medium  learning motivation were better  than the ones with the low learning motivation, 3) in students with high learning motivation, students who use macromedia flash have a learning achievement were better than using powerpoint. Students with medium and low learning motivation have the same learning achievement, using either the macromedia flash or powerpoint, 4) in mathematics learning with macromedia flash, students who have high motivation have better math achievement of students with medium and low motivation. But the students who have medium and low motivation the achievement were equally as good. In mathematics learning used powerpoint, students who have high, medium and low learning motivation have the same learning achievement.Keywords: Learning, Macromedia Flash, PowerPoint, Motivation, Achievement Learning Mathematics.